Marabou Stork Nightmares - Irvine Welsh (Great Britain Vintage, 2004)
Roy Strang is engaged in a strange quest in a surrealist South Africa. His mission is to eradicate an evil predator-scavenger bird, the marabou stork, before it drives away the peace-loving flamingo from the picturesque Lake Torto. But behind this world lies another: the world of Roy's bizarre family, the Scottish housing scheme in which he grew up, his mundane job, a disastrous emigration to Africa, and his youthful life of brutality with a gang of soccer casuals. As one world crashes into the other, this potentially charming story of ornithological goodwill mutates into a filthy tale of violence, abuse and redemption.
Keywords: Fiction; Mystery; Crime; Thriller; Short Stories